Understanding Key Concepts in Educational Research Through a Review of Two Research Articles - Budairi, Ahmad (Universitas Ahmad Dahlan, 2016)
This paper is intended to help novice researchers understand key concepts in educational research, particularly in the field of language education. It uses as its samples two peer-reviewed research articles on early childhood literacy development, bilingual and multilingual issues and identity consitution. ItÂ first attempts to analyze how the key concepts in educational research were incorporated into the research process. Of particular importance, this paper critically looks at the extent to which those key concepts were logically linked so as to provide the research with strong coherence. The discussion also takes into account the issues of ethics, how this was sufficiently dealt with by the author and what possible factors might have come into play to degrade the validity of the research. This paper conludes with my views on the research design and process as a whole and my suggestions on some of the issues uncovered during the discussion.Â